Answer:
Step-by-step explanation:(g o f)(-7) is a composite function.
It means that we are going to substitute each x in the g function with f(x) and then substitute in the final expression with x = -7
Therefore, we will do this on two steps as follows:1- getting (g o f)(x):we have:
f (x) = x² + 6
g (x) =
![(x+8)/(x)](https://img.qammunity.org/2019/formulas/mathematics/high-school/sofyobtco3t7063ct52ce1u34oa0548698.png)
Therefore:
(g o f)(x) =
2- getting (g o f)(-7):We will simply substitute with x = -7 in the expression obtained from part 1 as follows:
(g o f)(x) =
![(x^2+14)/(x^2+6)](https://img.qammunity.org/2019/formulas/mathematics/high-school/u9b7aqskmv6msjc0vkc1x78l5onz622yoh.png)
(g o f)(x) =
![((-7)^2+14)/((-7)^2+6)](https://img.qammunity.org/2019/formulas/mathematics/high-school/4hewgymrgceob29iwe5mkvx4mqdwutolog.png)
=
![(63)/(55)](https://img.qammunity.org/2019/formulas/mathematics/high-school/hoaanpcvemg8pnjnzqh7ihrzbwhwdhh754.png)
Hope this helps :)